Attractions to Fuel the Imagination: Reframing Understandings of the Role of Distraction Relative to Well-Being in the Pediatric Hospital. (April 2019) - McLaughlan, Rebecca; Sadek, Ahmed; Willis, Julie
Objective: Ulrich's (1991) definition of "positive distraction" includes that which "elicits positive feelings and holds attention, " implying that the capacity of an environmental feature to hold attention is a necessary component. This article examines whether, in the context of a pediatric hospital, a distraction needs to "hold attention" to secure positive benefits for patient well-being. Background: Data collected from 246 patients at Melbourne's Royal Children's Hospital (Australia) revealed a discrepancy between what children and young people told us they did, and valued, within the hospital, relative to the time they spent engaging in, or paying attention to, these same features. This motivated a closer interrogation of the relationship between well-being, distraction, and socialization within the pediatric context. Method: Data were collected using a mixed-methods approach that included 178 surveys, 43 drawings contributed by patients/siblings within the outpatient waiting room, 25 photo-elicitation interviews with patients, and 100 hr of spatial observations within public and waiting room spaces. This was supplemented by interviews with architects and hospital staff. Conclusions: The mechanism by which we have understood positive distraction to contribute to well-being within the pediatric hospital environment is more complex than existing models accept. Within this context, environmental features that can positively transform expectations of visiting the hospital—that can ignite the imagination and incite a desire to return—can offer significant benefits to well-being. This is particularly relevant in the context of absenteeism from outpatient appointments and in reducing patient resistance to future, or ongoing, treatments.